What’s All the Chatter? A Mixed-Methods Analysis of Emergency Physicians’ Tweets - Jeff Riddell; Alisha Brown; Lynne Robins; Rafae Nauman; Jeanette Yang; Joshua Jauregui (Western Journal of Emergency Medicine, 2019)
Introduction: Twitter is growing in popularity and influence among emergency physicians (EP), with over 2200 self-identified EP users. As Twitter’s popularity has increased among EPs so too has its influence. While there has been debate about the value of Twitter as an effective educational delivery tool, little attention has been paid to the nature of the conversation occurring on Twitter. We aim to describe how influential EPs use Twitter by characterizing the language, purpose, frequencies, content, and degree of engagement of their tweets. Methods: We performed a mixed-methods analysis following a combined content analysis approach. We conducted qualitative and quantitative analyses of a sample of tweets from the 61 most influential EPs on Twitter. We present descriptive tweet characteristics and noteworthy themes. Results: We analyzed 1375 unique tweets from 57 unique users, representing 93% of the influential Twitter EPs. A majority of tweets (1104/1375, 80%) elicited some response in the form of retweets, likes, or replies, demonstrating community engagement. The qualitative analysis identified 15 distinct categories of tweets. Conclusion: Influential EPs on Twitter were engaged in largely medical conversations in which most messages generated some form of interaction. They shared resources and opinions while also building social rapport in a community of practice. This data can help EPs make informed decisions about social media engagement.